Local anticorrelation between star formation rate and gas-phase metallicity in disc galaxies. Issue 4 (24th February 2018) - Sánchez Almeida, J; Caon, N; Muñoz-Tuñón, C; Filho, M; Cerviño, M
Abstract: Using a representative sample of 14 star-forming dwarf galaxies in the local Universe, we show the existence of a spaxel-to-spaxel anticorrelation between the index N2 $\equiv \, \log ({\rm [\rm N\, \small {II}]}\lambda 6583/{\rm H}\, \alpha )$ and the H α flux. These two quantities are commonly employed as proxies for gas-phase metallicity and star formation rate (SFR), respectively. Thus, the observed N2 to H α relation may reflect the existence of an anticorrelation between the metallicity of the gas forming stars and the SFR it induces. Such an anticorrelation is to be expected if variable external metal-poor gas fuels the star-formation process. Alternatively, it can result from the contamination of the star-forming gas by stellar winds and SNe, provided that intense outflows drive most of the metals out of the star-forming regions. We also explore the possibility that the observed anticorrelation is due to variations in the physical conditions of the emitting gas, other than metallicity. Using alternative methods to compute metallicity, as well as previous observations of H ii regions and photoionization models, we conclude that this possibility is unlikely. The radial gradient of metallicity characterizing disc galaxies does not produce the correlation either.